Enhanced Real-Time Multiuser Uplink UWOC System Based on Hybrid Multiple Access and SGD-PID Power Control Algorithm - Li, Xiao; Xia, Yu; Gui, Liangqi; Li, Han; Lang, Liang (Journal of lightwave technology, 2025)
Non-orthogonal multiple access (NOMA) has been widely regarded as the most promising technique for achieving high spectral efficiency in optical communication systems. However, the practical implementation of power domain NOMA faces challenges related to inter-user interference and decoding complexity, limiting its multiplexing capability to a pair of users. In this paper, we experimentally demonstrate a hybrid multiple access scheme in the four-user underwater wireless optical communication (UWOC) system. Specifically, power domain NOMA is employed to multiplex two users within a user pair (UP), while time division multiple access (TDMA) is utilized for each UP. To validate the efficacy of the hybrid multiple access technique, robust watertight transceivers are designed and implemented in a 10-m outdoor pool. A calculation method based on the channel condition is first introduced to retain the received power within a proper range when users in the UP are randomly positioned. Besides, an adaptive stochastic gradient descent-based proportional-integral-derivation (SGD-PID) algorithm is proposed for practical scenarios where determining the system and channel parameters is difficult. Experimental results show that the proposed adaptive power control schemes can effectively enhance system performance under different channel conditions experienced by users. The UWOC system achieves a data rate of 30 Mbps for each user, maintaining bit error rates (BERs) below forward error correction (FEC) threshold. The results highlight the remarkable potential of the hybrid multiple access scheme along with our proposed adaptive power control algorithm.